Given
"x^2p^2+xyp+2y^2=0" Let us denote "xp=q" ,thus we get "q^2+yq+2y^2=0" , now solving q ,we get,
"q=\\frac{-y\\pm\\sqrt{y^2-4\\cdot 1\\cdot 2y^2}}{2}\\\\\n\\implies q=\\frac{-y\\pm y\\sqrt{7}i}{2}\\\\\n\\implies xp=x\\frac{dy}{dx}=y(-1\\pm\\sqrt{7}i)\\\\\n\\implies \\frac{dy}{y}=(-1\\pm\\sqrt{7}i)\\frac{dx}{x}\\\\\n\\implies \\int\\frac{dy}{y}=(-1\\pm\\sqrt{7}i)\\int\\frac{dx}{x}\\\\\n\\implies \\ln y=-1\\pm\\sqrt{7}i\\ln x+\\ln c\\\\\n\\implies y=cx^{-1\\pm\\sqrt{7}i}" Where c is constant and "i=\\sqrt{-1}"
Comments
Leave a comment